Quem vê capa não vê tudo - as metáforas da infidelidade e do mistério na apresentação de Isabella Lubrano de Dom Casmurro no canal no youtube "ler antes de morrer" - Grigolo, Daniele (2021)
This research investigates2 the ‘infidelity’ and ‘mystery’ metaphors in the presentation of Dom Casmurro (1899), by Machado de Assis, performed by Isabella Lubrano, on the Ler antes de morrer channel, on YouTube platform. The analyzed video is entitled Dom Casmurro, de Machado de Assis (# 54) and was published on December 18, 2015. The analysis of the video in question comprises three distinct moments. The first is related to the description of Lubrano's video, with the objective of analyzing metaphors and their slips. Isabella starts the video from the cover illustration of the novel (39th edition of the publisher Ática, in 2006), pointing out, in this element, the presence of the ‘infidelity’ metaphor. Throughout the presentation, she desconstructs that first image and slides until it reaches the ‘mystery’ metaphor, that reflects your reading proposal. The second movement of analysis verifies how literary criticism treated these reading metaphors, present in two moments of Dom Casmurro's reception: the 'infidelity' metaphor is seen and suggested by critics until the 1960s, as the image of the 'mystery' comes after this period. Considering this, this work addresses four criticisms related to the image of ‘infidelity’, two published by José Veríssimo (1900; 1915), the third by Alfredo Pujol (1917) and fourth by Lúcia Miguel Pereira (1939). In the sequence, it analyzes criticisms that cover the 'mystery' metaphor, written by critics like Helen Caldwell (1960), Hélio de Seixas Guimarães (2004), João Cezar de Castro Rocha (2006; 2015), Roberto Schwarz (1990), Silviano Santiago ([1978] 2000) and Bosi ([2000] 2007). Therefore, the analysis of these metaphors is based on the study of criticism and emphasizes the way in which Machado's novel was received in each of them. Finally, the third research movement investigates the role of criticism as a presenter of texts through metaphors, which, in turn, plays a fundamental role in the reading mediation process.